2021
DOI: 10.3390/molecules26133781
|View full text |Cite
|
Sign up to set email alerts
|

Novel Spray Dried Algae-Rosemary Particles Attenuate Pollution-Induced Skin Damage

Abstract: The present study investigated the effect of spray-dried algae-rosemary particles against pollution-induced damage using ex-vivo human biopsies exposed to diesel engine exhaust (DEE). For this, the complexation of hydroalcoholic rosemary extract with Chlorella (RCH) and Spirulina (RSP) protein powders was conducted. The process efficiency and concentration of rosmarinic acid (RA), carnosic acid (CA), and carnosol (CR) phenolic compounds of both products were compared. The RSP spray-dried production was more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…It was found that long-term supplementation improved all clinical–biochemical parameters monitored, including increased skin elasticity, reinforced skin barrier function and a reduction in wrinkle depth and black spots in the enrolled patients [ 45 ]. Hoskin et al demonstrated, for the first time, the effective action of the topical application of a gel based on hydroalcoholic rosemary extract complexed with algae proteins on pollution-induced oxidative skin damage [ 46 ]. The emerging molecular mechanisms through which rosemary phenolic diterpenes acts are the inhibition of the increasing levels of active metalloproteinase-9 (MMP-9), the reduction of protein adducts formation and the reduction of filaggrin loss, which are induced by dermal exposure to diesel engine exhausts (DEE).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that long-term supplementation improved all clinical–biochemical parameters monitored, including increased skin elasticity, reinforced skin barrier function and a reduction in wrinkle depth and black spots in the enrolled patients [ 45 ]. Hoskin et al demonstrated, for the first time, the effective action of the topical application of a gel based on hydroalcoholic rosemary extract complexed with algae proteins on pollution-induced oxidative skin damage [ 46 ]. The emerging molecular mechanisms through which rosemary phenolic diterpenes acts are the inhibition of the increasing levels of active metalloproteinase-9 (MMP-9), the reduction of protein adducts formation and the reduction of filaggrin loss, which are induced by dermal exposure to diesel engine exhausts (DEE).…”
Section: Resultsmentioning
confidence: 99%
“…Penetration of pollutants into skin is not completely elucidated yet either, but a recent study showed that topical diesel engine exhaust penetrated into the dermis and activated MMP-9 in ex vivo cultured human skin [ 36 ]. Thus, MMP-1 and MMP-3 could be activated in skin following exposure to DPE.…”
Section: Discussionmentioning
confidence: 99%
“…Established protocols previously reported by our team were used to produce spray‐dried protein–polyphenol particles (Grace et al., 2022; Hoskin et al., 2021, 2022). At least three independent batches of each treatment were prepared using a spray dryer B‐290 (Buchi Labortechnik) in co‐current flow and with previously optimized conditions: 0.7 mm nozzle, 10 mL/min of feed flow (controlled by peristaltic pump), and drying air inlet temperature of 160°C (defined in preliminary experiments, data not shown) and outlet temperature of 80–84°C.…”
Section: Methodsmentioning
confidence: 99%
“…The solids recovery of spray‐dried protein–polyphenol samples was calculated as percentage (%) according to the ratio [total solids content of resulting particles / total solids content in the feeding mixture (before spray drying)] × 100, according to our previous protocol (Hoskin et al., 2021). In addition, the percentage (%) total polyphenol (TP) retention was determined as the ratio [TP of spray dried powder, mg/g) × (solids in powder, g)] / (TP of feed mixture, mg/g) × (solids in feed mix, g) × 100 (Zhang et al., 2020).…”
Section: Methodsmentioning
confidence: 99%